2013
DOI: 10.4038/seajme.v7i1.144
|View full text |Cite
|
Sign up to set email alerts
|

Exploring attributes of effective teachers – student perspectives from an Indian medical school

Abstract: Introduction: Attributes of an effective teacher is a passionate area of research for medical educators. Teaching at Melaka Manipal Medical College (MMMC), Manipal University, India, is assessed periodically as a part of the institution's program evaluation process. The present study was undertaken to determine the highly rated attributes of a medical teacher, as felt by three batches (preclinical, para-clinical and clinical batch) of medical students at MMMC. Methods: A questionnaire focusing on twelve attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Similarly, Ciraj et al found that motivation, defining objectives, communication, and showing respect to students were the major factors that students want to see in their teachers. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ciraj et al found that motivation, defining objectives, communication, and showing respect to students were the major factors that students want to see in their teachers. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Awareness of the expectations of students may help teachers to modify their approach to students and make teaching more effective. Ciraj et al, (2013)found the "ability to motivate" as the most desired attribute selected by students whereas in this study, only the late clinical students included this as one of the top ten attributes. Teachers in the study by Singh et al (2013) selected "knowledge of the subject" as the top desired attribute.…”
Section: Discussionmentioning
confidence: 99%
“…On this take we could make clear evaluation grids to encourage some behaviours and discourage other actions, to obtain best result and create better organisational culture. Teachers' knowledge, skills, and beliefs (Coles et al, 2015;Rubie-Davies et al, 2011), characteristics (Wayne et al, 2003Teven, 2009;Kukla-Acevedo, 2007;Danişman et al, 2018), qualities (Nghia, 2015), efficacy (Klassen et al, 2010;Dibapile, 2012), competencies (Chan, 2001;Shidiq et al, 2022), attributes (Ciraj et al, 2013), cognitive abilities (Bardach & Klassen, 2020) and conceptions (Barnes et al, 2017) all influence pupils' result and performance, teachers' wellbeing (Konu & Viitanen, 2010), class management, career development, and lifelong learning perception for both teachers and pupils.…”
Section: Literature Reviewmentioning
confidence: 99%